Microalgae from biorefinery as potential protein source for siberian sturgeon (A. baerii) aquafeed - Bongiorno T.; Foglio L.; Proietti L.; Vasconi M.; Lopez A.; Pizzera A.; Carminati D.; Tava A.; Vizcaino A. J.; Alarcon F. J.; Ficara E.; Parati K. (Sustainability, 2020)
The demand for aquafeed is expected to increase in the coming years and new ingredients will be needed to compensate for the low fish meal and oil availability. Microalgae represent a promising matrix for the future aquafeed formulation, however, the high production cost hinders its application. The use of microalgae from biorefinery would reduce the disposal costs for microalgae production. The present study aimed to (i) verify the growth of microalgae on digestate coming from pig farming and (ii) evaluate their potential valorization as dietary ingredient in aquafeed according to a Circular Bioeconomy approach. For these purposes, a microalgae biomass was produced on an outdoor raceway reactor supplied with digestate and used for partial replacement (10% of the diet) in aquafeed for Siberian sturgeon fingerlings (Acipenser baerii). The results obtained confirm the feasibility for growing microalgae on digestate with satisfactory productivity (6.2 gDM m-2 d-1), nutrient removal efficiency and Chemical Oxygen Demand reduction; moreover, the feeding trial carried out showed similar results between experimental and control groups (p > 0.05), in term of growth performance, somatic indices, fillet nutritional composition and intestinal functionality, to indicate that microalgae from biorefinery could be used as protein source in Siberian sturgeon aquafeed.